2007
DOI: 10.1128/jvi.01580-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutually Exclusive T-Cell Receptor Induction and Differential Susceptibility to Human Immunodeficiency Virus Type 1 Mutational Escape Associated with a Two-Amino-Acid Difference between HLA Class I Subtypes

Abstract: The relative contributions of HLA alleles and T-cell receptors (TCRs) to the prevention of mutational viral escape are unclear. Here, we examined human immunodeficiency virus type 1 (HIV-1)-specific CD8 ؉ T-cell responses restricted by two closely related HLA class I alleles, B*5701 and B*5703, that differ by two amino acids but are both associated with a dominant response to the same HIV-1 Gag epitope KF11 (KAFSPEVIP MF). When this epitope is presented by HLA-B*5701, it induces a TCR repertoire that is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
79
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 41 publications
11
79
3
Order By: Relevance
“…One explanation is that the TV9:HLA-A*0202 complex may elicit a more effective T cell repertoire than the corresponding TV9: HLA-A*0201 complex. Indeed, there is precedence that closely related HLA class I alleles (HLA-B*5701 and HLA-B*5703) can recruit dissimilar and differentially effective CD8 ϩ T cell repertoires during infection (81).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation is that the TV9:HLA-A*0202 complex may elicit a more effective T cell repertoire than the corresponding TV9: HLA-A*0201 complex. Indeed, there is precedence that closely related HLA class I alleles (HLA-B*5701 and HLA-B*5703) can recruit dissimilar and differentially effective CD8 ϩ T cell repertoires during infection (81).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 peptides TLNAWVKVV (TV9, Gag p24 19 -27 ), TLNAWVKVI (9I), TLNAWVKLV (HIV-2 Gag, 8L), SLYNTVATL (SL9, Gag p17 [77][78][79][80][81][82][83][84][85] ), SLFNTVATL (3F), SLYNTVAAL (SL9 agonist, p41), ILKEPVHGV (IV9, Pol 476 -484 ), the influenza matrix peptide GILGFVFTL (GL9, Flu MP 58 -66 ), and the tyrosinase 368 -376 peptide YMNGTMSQV (YV9) were synthesized by Genemed Synthesis. The purity and identity of each peptide were verified by electrospray mass spectrometry interfaced with liquid chromatography.…”
Section: Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HLA B*5703-restricted responses had more diverse TCR usage and more in vivo variation of the KF11 epitope, yet were unable to recognize in vivo HIV variants. These researchers concluded that a two amino acid difference between the HLA B*5701 and B*5703 alleles was likely responsible for the HIV epitope variation seen in HLA B*5703 subjects, and consequently these subjects had more diverse TCR repertoires (18). While it remains unclear whether TCR diversity is a prerequisite for control of HIV-1 viremia, the structure of the TCR repertoire is the driving force behind the immune system's ability to recognize and respond to virus variants.…”
mentioning
confidence: 99%
“…In previous work, Gillespie et al (17) found conserved TCR variable region ␤ (TRBV) 4 usage (TRBV19) and highly conserved CDR3 region motifs among isolated CTL clones from three out of five subjects recognizing the KF11 epitope. Yu et al (18) more recently studied TCR usage of KF11-specific T cells and found that HLA B*5701 subjects had striking usage of TRBV19 with shared CDR3 motifs, very little variation of the circulating KF11 epitope, and these TCRs displayed cross reactivity to published KF11 variants. In contrast, HLA B*5703-restricted responses had more diverse TCR usage and more in vivo variation of the KF11 epitope, yet were unable to recognize in vivo HIV variants.…”
mentioning
confidence: 99%